2022
DOI: 10.3390/nano12111784
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Grinding Method for Preparing Ultra-Thin Boron Nanosheets

Abstract: The preparation of boron nanosheets has very strict requirements of the preparation environment and substrate. In this work, the boron nanosheets were tried to prepare by the grinding method, using β-B alloy with stable chemical properties and large crystal plane spacing. Its morphology and chemical bonds of boron nanosheets were analyzed by scanning microscope (SEM), transmission microscope (TEM), and X-ray photoelectron spectroscopy (XPS). The results show that the two-dimensional boron nanosheets can be pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Nishino et al 100 found that ultrasonic dissociation of MgB 2 in water produces Mg-deficient hydroxyl-functionalized BNSs at room temperature. Wang et al 101 discovered that 2D BNSs could also be obtained by simply grinding boron powder with an agate mortar after HNO 3 etching of Cu-5B alloy, but that the resulting BNSs have a large thickness and a high degree of oxidation.…”
Section: Two-dimension (2d) Boron Nanomaterialsmentioning
confidence: 99%
“…Nishino et al 100 found that ultrasonic dissociation of MgB 2 in water produces Mg-deficient hydroxyl-functionalized BNSs at room temperature. Wang et al 101 discovered that 2D BNSs could also be obtained by simply grinding boron powder with an agate mortar after HNO 3 etching of Cu-5B alloy, but that the resulting BNSs have a large thickness and a high degree of oxidation.…”
Section: Two-dimension (2d) Boron Nanomaterialsmentioning
confidence: 99%